MOSAIC OR JIGSAW? PUBLISHING AN ARTICLE FROM ESTONIA IN THE “WEST”, 30 YEARS AGO, WHEN CIRCUMSTANCES WERE QUITE DIFFERENT FROM TODAY - Grzybek, Peter (Proverbium - Yearbook, 2014)
The communication from April until November 1984 be-tween Arvo Krikmann from Estonia and myself (at that time living in Germany) is from a time, when there was no electronic communication, neither written (be that by email or sms), nor spoken (via mobiles, skype, or similar media). It was a time, when “ordinary” letters or telegrams were written, and when “ordinary” telephones were used for spoken communication – provided there were open lines and connections, which was the case only to a very limited degree when communicating with members of the former Soviet Union. Despite such restrictions, particularly concerning communication across political boundaries, and despite analogical options and desires to control communication in our days, one advantage of the “old” communication media is that they are likely to be saved for a longer time than our modern ones, and that they thus can serve as documents not only of personal or inter-personal relations, but also of a specific period, both in political and academic respects.